Systemic inflammation-based Glasgow Prognostic Score as a prognostic indicator in chronic heart failure - Shigeto Namiuchi; Kotaro Nochioka; Ryoichi Ushigome; Shinichiro Sunamura; Atsushi Tanita; Tsuyoshi Ogata; Kazuki Noda; Toru Takii; Hiroaki Shimokawa; Satoshi Yasuda (International Journal of Cardiology: Heart & Vasculature)
Background: The Glasgow Prognostic Score (GPS), based on C-reactive protein and serum albumin concentrations provides useful prognostic information for patients with cancer or acute decompensated heart failure (HF). Herein, we aimed to evaluate the relationship between the GPS and long-term prognosis in patients with chronic HF. Methods: In this large multicentre prospective observational study, part of the Chronic Heart Failure Analysis and Registry in the Tohoku District-2 (CHART-2) Study, we analysed the relationship between mortality and the GPS in 6,480 patients with chronic HF (mean age, 68 ± 13 years; 69 % male). Patients with elevated C-reactive protein levels (>1.0 mg/dL) and hypoalbuminaemia (<3.5 g/dL) received a GPS of 2; those with either received a GPS of 1, and those with neither received a GPS of 0. Results: During median follow-up of 9.62 years, 2,564 patients (39.6 %) died. Increased GPS was associated with a significantly higher mortality risk in Kaplan–Meier analysis (log-rank P < 0.0001). This trend was consistent across sex, age, New York Heart Association class, HF stage and type, and cancer history. Adjusted Cox proportional hazards analysis showed the following hazard ratios for all-cause death, relative to a GPS of 0, 1.27 (95 % confidence interval, 1.13–1.44; P < 0.0001) for a GPS of 1 and 1.83 (95 % confidence interval, 1.45–2.32; P < 0.0001) for a GPS of 2. This increased risk was independent of B-type natriuretic peptide levels. Conclusions: The GPS, which reflects systemic inflammation status, is a useful predictor of long-term prognosis in patients with chronic HF.